A single‐surface wideband printed monopole antenna with high‐order mode compression by bending line loading. Issue 1 (7th October 2022) - Zhao, Songjiang; Luo, Yu
Abstract: A wideband coplanar waveguide‐fed printed monopole antenna is proposed. The wideband performance of the monopole is achieved by compressing the third‐ and fifth‐order modes. By loading the bending line at the zero point of the third‐order mode of the monopole current distribution, the fifth‐order mode resonant frequency decreases significantly, while the third‐order mode resonant frequency remains almost constant. Therefore, a wideband impedance match is achieved. A fully functional prototype was fabricated and characterized. The measured results are in good agreement with the simulated results. A wideband from 2.92 to 3.66 GHz (22.5%) was achieved in a thin structure of 85 × 33 mm 2, exhibiting a measured omnidirectional radiation pattern with 2.4–4.9 dBi gain.